1980
DOI: 10.1128/iai.28.1.163-170.1980
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Immunization with Heat-Labile Enterotoxin in Gnotobiotic Rats Monocontaminated with Enterotoxigenic Escherichia coli

Abstract: The protective effect of active immunization with a purified preparation of the polymyxin-release form of Escherichia coli heat-labile enterotoxin (LT), administered using a parenteral prime and peroral boosts given after ablation of gastric secretion by means of cimetidine, was assessed in gnotobiotic rats which were challenged by monocontamination with enterotoxigenic strains of E. coli. Water transport was evaluated by the in vivo marker perfusion technique at weekly intervals over a 3-week period after con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Protection was greater against the LT-only strain than against the LT'/ST' strain in all animals immunized by the IP/IP route, but such was not always the case when immunization was given by the IP/PO route. The factors responsible for protection against a strain which produces both LT and ST are uncertain; we have speculated that in this circumstance the observed protection is directed against the LT produced by this strain (19,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protection was greater against the LT-only strain than against the LT'/ST' strain in all animals immunized by the IP/IP route, but such was not always the case when immunization was given by the IP/PO route. The factors responsible for protection against a strain which produces both LT and ST are uncertain; we have speculated that in this circumstance the observed protection is directed against the LT produced by this strain (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…The validity of these observations, which utilized the ligated ileal loop model, to circumstances that more closely resemble the actual disease state of intestinal colonization by enterotoxigenic E. coli strains has been confirmed. Immunization with PM LT given by the IP/PO route has been shown to provide protection against the secretory effect of intestinal colonization by enterotoxigenic strains of E. coli which produce either LT alone (LT'/ ST-) or in combination with the heat-stable (ST) toxin (LT+/ST+) in gnotobiotic rats (20).…”
mentioning
confidence: 99%
“…The degree of protection was less in some instances when the toxins were given exclusively by the parenteral route, and the B subunit failed to provide any protection whatsoever against the LT'/ST' strain when given by this approach. It seems probable that the protection against this strain that is induced by immunization with LT toxin forms is directed against the LT produced by this strain (22). We suspect that the lesser degree of protection that was observed in some instances in animals immunized exclusively by the parenteral route was due to the fact that this approach stimulates principally systemic IgG antibodies, whereas the combined parenteral-PO immunization regimen provides protection derived from both systemic antibodies and IgA antibodies produced locally within the intestinal mucosa (25,32,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The first demonstrated that in rats immunized with various different regimens and dosages of PM LT, those which had a PI > 5 against challenge with the toxin also consistently had >50% reduced secretion when challenged by the LT+/STstrain (21). The second study showed that immunization with those dosages which yield these values in ligated loops also provides protection against the secretory effect of intestinal colonization with either an LT+/STor an LT'/ST' strain in gnotobiotic rats (22).…”
Section: Methodsmentioning
confidence: 97%
“…The results of the present study establish the effectiveness of immunization with this vaccine in a second experimental animal model, rabbits. Protection in both animal models was demonstrated by means of challenge in ligated ileal loops; the applicability of this technique to protection under challenge conditions in which the entire intact intestine is colonized by LT-producing enterotoxigenic strains of E. coli has been confirmed in gnotobiotic rats immunized with LT (20).…”
Section: Discussionmentioning
confidence: 92%